Reconstruction of the TMJ and condyle in inflammatory arthritis - Andrew Henry; Pushkar Mehra (Elsevier, 2022)
Inflammatory arthritis presents a unique destructive process to the temporomandibular joint. This article provides information on the proper diagnosis, treatment planning, and surgical management aimed to provide patients with improvement in pain, function, stability and facial aesthetics. Additionally, it aims to provide a detailed insight on the joint reconstruction options including alloplastic joint replacement, autogenous joint replacement, orthognathic surgery and distraction osteogenesis.